A UNIFIED MODEL FOR ANALYZING DIMENSIONAL RELATIONSHIPS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents an attempt to introduce an integrated model for analysing dimensional relationships. The basis for the application of a unified approach in revealing, analysing and solving the dimensional chains is the fact that each element of the dimensional relationships in the product has a spatial expression. The practical side of the proposed unified model for the analysis of dimensional relationships is also presented. The essence of this model is that a single approach is applied to solve all dimensional chains, regardless of their spatial location. The model represents the dimensional chain by the coordinates of a sequence of basic points, the distances between which determine the components of the dimensional chain.